Incidence, Prevalence And Risk Factors For Comorbid Mental Illness Among People With Hypertension And Type 2 Diabetes In West Africa: Protocol For A Systematic Review And Meta-Analysis. - Amoakoh-Coleman, M.; Mirzoev, M.; Agyepong, I.A.; Ohene, S.; Awini, E.; Antwi, E.; et al. (BMJ Open, 2024)
Introduction Mental illness remains a significant global health concern that affects diverse populations, including individuals living with hypertension and/ or type 2 diabetes, predominantly in lower-income to middle-income countries. The association between non-communicable diseases (NCDs) and mental illness is firmly established globally, however, this connection has yet to be comprehensively explored in West Africa. Our systematic review and meta-analysis aim to synthesise existing evidence on the prevalence, incidence, and risk factors for comorbid mental illness with hypertension and/or type 2 diabetes in West Africa. This effort seeks to contribute to bridging the knowledge gap and facilitating the implementation of interventions tailored to this context. Methods and analysis A comprehensive search will be conducted across multiple databases (PubMed, Google Scholar, PsycINFO, Carin Info and CINAHL), supplemented by searches on the websites of the WHO and various countries’ ministries of health, and references cited in relevant papers. Inclusion criteria specify studies conducted in countries from the Economic Community of West African States, reported from January 2000 until date of search, focusing on adults with hypertension and/ or type 2 diabetes and mental illness. Exclusion criteria encompass studies outside the specified time frame, involving pregnant women, or lacking relevant outcomes. There will be no language restrictions for inclusion. Study selection, data extraction and risk of bias assessment will be carried out independently by at least two reviewers. We will employ pooled proportions of OR, risk ratio and mean differences to assess prevalence, and incidence of mental illness and heterogeneity will be assessed. Ethics and dissemination This protocol does not require ethical approval; however, it is a part of a larger study on NCDs, which has received ethical clearance from the Ghana Health Service (ID NO: GHS-ERC 013/02/23). The results will be presented to stakeholders (policymakers and practitioners) and disseminated through conferences and peer-reviewed publications. PROSPERO registration number CRD42023450732. The study employs a robust, structured methodology to ensure a comprehensive analysis of the available literature, facilitating a thorough examination of the relationship between mental illness and coexisting hypertension and/or type 2 diabetes within the West African context. ⇒ By following predefined inclusion and exclusion criteria, this protocol minimises selection bias and ensures the transparency and replicability of the review process. ⇒ A possible limitation is the unavailability of previous data to compare our review with as this is the first review performed to investigate the incidence and prevalence of mental illness among people living with hypertension and/or type 2 diabetes in West Africa.
Research Article
Keywords: Mental Illness; Hypertension; Type 2 Diabetes; West Africa